2023
DOI: 10.1186/s12934-023-02071-9
|View full text |Cite
|
Sign up to set email alerts
|

High-efficient production of mushroom polyketide compounds in a platform host Aspergillus oryzae

Abstract: Background Orsellinic acid (2,4-dihydroxy-6-methylbenzoic acid, OA) and its structural analog o-Orsellinaldehyde, have become widely used intermediates in clinical drugs synthesis. Although the research on the biosynthesis of such compounds has made significant progress, due to the lack of suitable hosts, there is still far from the industrial production of such compounds based on synthetic biology. Results With the help of genome mining, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…The sequencing results of RNA extracted from AO-flaX transformants and reverse transcribed into cDNA showed that the introns in these genes were correctly spliced. In previous studies, we used the A. oryzae expression system not only heterologously production diterpene 31−33 and polyketide compounds from basidiomycetes 34 but also identify the functions of 31 STSs from two basidiomycota fungi, C. pseudopinsitus and S. hirsutum, 12 demonstrating that A. oryzae is both an excellent expression host for basidiomycetes and has abundant FPP for the production of various terpenoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing results of RNA extracted from AO-flaX transformants and reverse transcribed into cDNA showed that the introns in these genes were correctly spliced. In previous studies, we used the A. oryzae expression system not only heterologously production diterpene 31−33 and polyketide compounds from basidiomycetes 34 but also identify the functions of 31 STSs from two basidiomycota fungi, C. pseudopinsitus and S. hirsutum, 12 demonstrating that A. oryzae is both an excellent expression host for basidiomycetes and has abundant FPP for the production of various terpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we used the A. oryzae expression system not only heterologously production diterpene and polyketide compounds from basidiomycetes but also identify the functions of 31 STSs from two basidiomycota fungi, C. pseudopinsitus and S.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Aspergillus oryzae is a convenient host, because it is a GRAS (generally regarded as safe) organism and produces none or very few own polyketides. It has been used to decipher the alternariol biosynthesis (Wenderoth et al., 2019) and more recently for the production of basidiomycete polyketides (Han et al., 2023). Another host organism is A. nidulans , which has been engineered by deletion of eight entire native BGCs from its genome for a cleaner background and less crosstalk between native and heterologous genes (Chiang et al., 2022).…”
Section: Sm Mining and “Biosynthetic Dark Matter”mentioning
confidence: 99%
“…For instance, Aspergillus oryzae is a convenient host, because it is a GRAS (generally regarded as safe) organism and produces none or very few own polyketides. It has been used to decipher the alternariol biosynthesis (Wenderoth et al, 2019) and more recently for the production of basidiomycete polyketides (Han et al, 2023).…”
Section: S M Mining and " B I Osynthe Ti C Dark Mat Ter "mentioning
confidence: 99%
“…Capitalizing on a robust capacity for protein synthesis, secretion, and posttranslational modification, A. oryzae has also shown potential for heterologous protein expression. Recently, the integration of heterologous pathways into the A. oryzae genome through precise genetic manipulation has yielded a diverse array of enzymes and secondary metabolites, exemplified by ergothioneine [5], orsellinic acid [6], chevalone E [7], abscisic acid [8], aphidicolin [9], and others. As genetic manipulation techniques continue to evolve, the utilization of A. oryzae as a host for heterologous protein expression is increasingly maturing.…”
Section: Introductionmentioning
confidence: 99%